Depression in adult Nigerians: results from the Nigerian Survey of Mental Health and Well-being (2010)
Background: Community-based studies of the rates and profile of depression among Africans are still sparse. Methods: As part of the World Mental Health Surveys initiative, a clustered multi-stage sampling of households in 21 of Nigeria's 36 states (representing 57% of the national population) was implemented to select adults aged 18 years and over(N=6752)for face-to-face interviews using the Composite International Diagnostic Interview (CIDI 3.0). Diagnosis of major depressive episode (MDE) was based on the criteria of the Diagnostic and Statistical Manual, 4th edition. Results: Lifetime and 12 monthestimatesofMDEwere3.1%(standarderror0.3) and1.1% (s.e.0.1), receptively. Increasing age was associated with higher estimates of positive responses to stem (screen)questions for depression and of lifetime disorders among stem-positive respondents. The mean age of onset was about 29.2 years. The median (inter quantile range, IQR) duration of an episode among lifetime cases was 1.0 (2.0–2.4) year and the median (IQR) number of lifetime episodes was 1.5 (2.0–2.8). MDE was highly comorbid with anxiety disorders, musculoskeletal conditions, chronic pain and ulcer. The odds ratio of lifetime suicide attempt among persons with lifetime MDEwas11.6(95%confidenceinterval,3.9–34.9).Over25%of12-monthcaseswererated as severely disabled in the performance of usual roles. Only 16.9%(i.e. 5.0) of 12-monthcases had received any treatment. Limitations: All data were based on self-reports. Conclusion: MDE, defined according to DSM-IV, is a risk factor for mental and physical comorbidity as well as disability in Nigerians. Age-related telescoping or denial may partly explain the low rates in this young population